Air Pollution Modeling and its Application XXV (Springer Proceedings in Complexity, 2018)
Current developments in air pollution modelling are explored as a series of contributions from researchers at the forefront of their field. This newest contribution on air pollution modelling and its application is focused on local, urban, regional and intercontinental modelling; long term modelling and trend analysis; data assimilation and air quality forecasting; model assessment and evaluation; aerosol transformation. Additionally, this work also examines the relationship between air quality and human health and the effects of climate change on air quality. This Work is a collection of selected papers presented at the 35th International Technical Meeting on Air Pollution Modeling and its Application, held in Chania (Crete), Greece, Oct 3-7, 2016. The book is intended as reference material for students and professors interested in air pollution modelling at the graduate level as well as researchers and professionals involved in developing and utilizing air pollution models.